2013
DOI: 10.1108/ijhma-01-2012-0003
|View full text |Cite
|
Sign up to set email alerts
|

The value of a floor: valuing floor level in high‐rise condominiums in San Diego

Abstract: Purpose-This paper aims to analyze the effect of floor level on condominium prices in San Diego, California. The authors determine whether "higher-floor premiums" exist in the condominium market for a large California city. Further, they investigate how the floor premium varies throughout a building, particularly whether it is quadratic and whether there is a "penthouse premium" for top-floor units. Design/methodology/approach-The paper utilizes a data set of 2,395 condominium sales occurring in San Diego betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 30 publications
1
23
3
1
Order By: Relevance
“…These factors would include fresh air (Kei, Wing, Yung, & Chung, 2006), better ventilation, much sunlight, better security, and lower humidity, which is important in Japan. Furthermore, high-rise units are often penthouse units, which have a positive premium (Conroy, Narwold, & Sandy, 2013). Thus, the positive sign of "Floor" is reasonable.…”
Section: Hedonic Analysis: Resultsmentioning
confidence: 94%
“…These factors would include fresh air (Kei, Wing, Yung, & Chung, 2006), better ventilation, much sunlight, better security, and lower humidity, which is important in Japan. Furthermore, high-rise units are often penthouse units, which have a positive premium (Conroy, Narwold, & Sandy, 2013). Thus, the positive sign of "Floor" is reasonable.…”
Section: Hedonic Analysis: Resultsmentioning
confidence: 94%
“…U nekim oglasima nije naveden sprat na kojem se stan nalazi. U ranijim radovima je ustanovljeno da sprat ima značajan uticaj na cenu stana [7], pa su oglasi bez navedenog sprata uklonjeni iz skupa podataka. Podaci o datumu objavljivanja i ažuriranja oglasa, kao i tipu oglašavača su uklonjeni iz skupa podataka, jer su vezani za sam oglas, a ne za nekretninu, pa ne bi trebalo da utiču na njenu cenu.…”
Section: Pretprocesiranje Podatakaunclassified
“…Conroy and Milosch (2011) noticed that 100 square foot rise in structure is tied with a 2.29% higher price. Conroy et al (2013) proved that 7.5 percent increase of price occur with every 100-foot rise in square footage. Kim et al (2015) revealed that apartment prices augment as size is near 134.5 square metres and then drops.…”
Section: Introductionmentioning
confidence: 99%
“…Conroy and Milosch (2011) revealed that an extra bathroom is related with a 4.3% upper sales price and Ibeas et al (2012) documented that the presence of an additional bathroom rises prices by 12%, having a garage lift prices by 10% and if the building is equipped with a lift the price rise by 20%. Conroy et al (2013) found that a supplemental bathroom generates a 5.3 percent lift in sales price, while an extra bedroom increases price by 9.9 percent. Also, Zhang and Yi (2017) contended that house price rises by 9.77% in case of one more bedroom and by 14.47% in case of one more living room.…”
Section: Introductionmentioning
confidence: 99%